Oral simethicone tablets with PEG‐ELS split‐prep reduces frequency of inadequate bowel cleansing and decreases bubbles. Issue 4 (17th July 2021) - Maratt, Jennifer K.; Freeman, Alison E.; Schoenfeld, Philip; Saini, Sameer D.; Su, Grace L.; Tai, Andrew W.; Prabhu, Anoop; Rubenstein, Joel H.; Waljee, Akbar K.; Glass, Lisa; Dang, Duyen; Parikh, Neehar D.; et al.
Abstract: Background: Intraluminal bubbles may prevent the visualisation of mucosa during a colonoscopy. Simethicone minimises bubbles, but its impact on incomplete bowel preparation and optimal protocols for use are unclear. Aim: To assess the impact of oral simethicone tablets when added to 2‐litre, split‐prep, polyethylene glycol electrolyte lavage solution + ascorbic acid on bubble score and frequency of incomplete bowel preparation. Methods: This QA/QI project assessed outpatients who underwent colonoscopy at the Veterans Affairs Ann Arbor Healthcare System. After endoscopists were trained in intraluminal bubble scoring systems, data about bubble score, frequency of inadequate bowel preparation requiring early repeat colonoscopy, quality of bowel preparation using Boston Bowel Preparation Scale (BBPS), and patient tolerance were collected before and after addition of oral simethicone 160mg to each dose of 2‐litre split‐prep. Results: There were no differences in patient characteristics between the baseline group (n = 348) and the simethicone group (n = 354). Simethicone improved the total mean intraluminal bubble score from 8.18 to 8.78 ( P < 0.001). Early repeat colonoscopy due to inadequate bowel preparation was higher in the baseline group vs simethicone group: 8.7% vs 4.6%, P = 0.03 with an RRR = 0.5 (95% CI 0.26‐0.95). Using BBPS, the frequency of having inadequate cleansing in any colon segment was higher in the baseline group vs simethicone group: 6.6% vs 3.1%; RRR = 0.55 (95% CI 0.21‐0.94). Conclusions: The addition of oral simethicone to each dose of 2‐litre, split‐prep of polyethylene glycol + ascorbic acid decreased intraluminal bubbles and reduced the frequency of inadequate bowel preparation.